Cover Feature: High‐Voltage Supercapacitors Based on Aqueous Electrolytes (ChemElectroChem 4/2019). Issue 4 (25th January 2019) - Zang, Xining; Shen, Caiwei; Sanghadasa, Mohan; Lin, Liwei
Abstract : The Cover Feature shows the typical structure of a supercapacitor working in aqueous electrolyte. Two electrodes (symmetric/asymmetric) are generally constructed with porous conductive materials. High voltage indicates a working range over the hydrolysis limit, which is 1.23 V. The Review discusses the design of electrodes and electrolytes to achieve high‐voltage supercapacitors in aqueous electrolyte. More information can be found in the Review by X. Zang et al. on page 976 in Issue 4, 2019 (DOI: 10.1002/celc.201801225 ).